Conductive herringbone structure carbon nanotube/thermoplastic polyurethane porous foam tuned by epoxy for high performance flexible piezoresistive sensor. (8th September 2017) - Wei, Xiangdong; Cao, Xiaohan; Wang, Yalong; Zheng, Guoqiang; Dai, Kun; Liu, Chuntai; Shen, Changyu
Abstract: In this paper, we used epoxy (EP) as a third component to tune the electromechanical performances of the conductive porous foam. A directional ice-template freezing method was utilized to fabricate a carbon nanotubes (CNTs)/EP/thermoplastic polyurethane (TPU) porous foam with a herringbone-like structure. CNTs were homogeneously distributed in the skeleton of the foam. The microstructure of the herringbone-like foam was studied in detail from both the directions perpendicular and parallel to the freezing front movement direction. An ultralow percolation threshold (0.088 vol%) of the conductive foam was achieved. The strength of the CNTs/TPU/EP foam was significantly enhanced with the increase of the CNTs and EP contents. When the foams were exposed to a compression strain from 0 to 70%, the resistance of the porous material decreased in a good linear manner. The foams showed a good differenciation capability towards different compression strain amplitude. Upon multiple cyclic compressive process, the change of the resistance tended to be stable after several compression loading-unloading cycles' measurement. After a pre-compression treatment, the resistance response also became much stable on the basis of the re-arrangement of the conductive network and the stabilized cells structure of the foam. The porous foam possesses a rapid response speed (about 160 ms). Our flexible porous foam with a good chemical resistance can be used in ethanol to sense the finger pressing, and it showed excellent sensing performances when applied to monitor human body motions.